Dysmetabolism and Neurodegeneration - Capucho, Adriana M. (2022)
Funding Information: Funding: AC and FOM were supported by grants and contracts from the Portuguese Foundation for Science and Technology, PD/BD/136863/2018 and CEECIND/04266/2017, respectively.